Effectiveness of workplace diabetes prevention programs: A systematic review of the evidence - Brown, Sharon A.; García, Alexandra A.; Zuñiga, Julie A.; Lewis, Kimberly A. (Patient education and counseling, 2018)
•A systematic review on diabetes-related workplace interventions was conducted.•Lifestyle interventions were delivered in groups of fewer than 20 employees.•One-hour weekly sessions were held during lunch hour for 12 to 24 weeks.•Outcomes, commonly measured at 6 and/or 12 months, were consistently positive. The primary purpose is to review diabetes workplace interventions and the degree to which they improve diabetes-related outcomes in employees diagnosed with or at risk for T2DM. Three electronic databases and ancestry searches were used to identify peer reviewed articles published in English from 2000 to June 2017. The number of participants represented by the 22 selected studies, excluding one large outlier, was 4243. On average, the samples were 57% female and ethnically diverse. Interventions—healthy eating behaviors, physical activity, and/or monitoring and self-managing diabetes and cardiovascular risk factors—were delivered in group sessions of fewer than 20 employees. Programs involved 1-h weekly sessions held during lunch hour or at other times during the workday for 12 to 24 weeks. Study outcomes, commonly measured at 6 and/or 12 months, were consistently positive. The literature search uncovered beginning evidence that workplace interventions hold promise for preventing diabetes and/or its complications. More rigorous, creatively designed, workplace studies, are needed for employees at high-risk for developing diabetes. Implications include the need for employer education about the benefits of employer support for such programs and attention to motivational strategies so employees will take full advantage of programs that are offered.